Dissection of cervico-cerebral arteries and cerebrovascular disease - L. A. Kalashnikova (Анналы клинической и экспериментальной неврологии, 2007)
Review of the literature and the authors own experience on thedissection of cervico-cerebral arteries leading to ischemic strokeand transient ischemic attacks are presented. Discussed areissues of etiology, clinical picture, differential diagnosis andtreatment of this from of pathology of cervico-cerebral arteries.Special attention is paid to modern possibilities of non-invasive invivo diagnosis of dissection of cervico-cerebral arteries on the basisof newest methods of computerized neuro- and angioimaging.